Evaluation of molecular mouse sepsis panel: new portable and rapid tests for microorganism detection in suspected blood stream infection - Colosimo, Claudia; Montanari, Maria Sofia; Marzucco, Anna; Gatti, Giulia; Puccini, Lucrezia; Grumiro, Laura; Dionisi, Laura; Brandolini, Martina; Ingletto, Ludovica; Guerra, Massimiliano; Dirani, Giorgio; Zannoli, Silvia; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBloodstream infections (BSIs) represent a significant public health concern, characterized by the presence of pathogens in the bloodstream, leading to serious conditions. Between 30 and 40% of BSIs evolve in sepsis, characterized by a life-threatening organ dysfunction and accompanied by a strong or dysregulated systemic immune or inflammatory response. A timely and accurate diagnosis of BSIs is crucial for ensuring effective management and treatment of critically ill patients. The diagnosis of BSIs can be initiated either from positive blood culture (BC) or directly from blood specimens using advanced diagnostic methods, these approaches are increasingly integrated into traditional diagnostic workflows.MethodsIn the context of emerging molecular methods, Alifax introduced the Molecular Mouse (MM) Sepsis Panel in 2022. This study aims to evaluate the performance of MM cartridges in detecting Gram-positive bacteria and Gram-negative bacteria, as well as their associated resistance genes, using clinical leftover positive BCs and contrived samples for low-prevalence targets. Positive BCs were collected at the Unit of Microbiology, The Great Romagna Hub Laboratory, Pievesestina, FC, Italy. ResultsOverall, MM Sepsis Panel showed excellent sensitivity (98.62%) and specificity (99.81%), confirming the system’s reliability and accuracy. DiscussionThe high diagnostic accuracy demonstrated by these tests supports their potential application as rapid diagnostic tools for blood cultures, facilitating prompt identification of pathogens and antimicrobial resistance determinants in clinical microbiology settings.